Overcoming hypoxia-induced tumor radioresistance in non-small cell lung cancer by targeting DNA-dependent protein kinase in combination with carbon ion irradiation - Klein, Carmen; Dokić, Ivana; Mairani, Andrea; Mein, Stewart; Brons, Stephan; Häring, Peter; Haberer, Thomas; Jäkel, Oliver; Zimmermann, Astrid; Zenke, Frank; Blaukat, Andree; Debus, Jürgen; et al. (Radiation oncology, 2017)
Hypoxia-induced radioresistance constitutes a major obstacle for a curative treatment of cancer. The aim of this study was to investigate effects of photon and carbon ion irradiation in combination with inhibitors of DNA-Damage Response (DDR) on tumor cell radiosensitivity under hypoxic conditions.